(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The impact of the structured learning strategy supported by hypermedia in learning the skills of handling and suppression in footballThe aim of the research is to design and implement educational units according to the self-regulated education strategy and to design a program for hypermedia according to the skills of handling and suppression in football. The researcher used the experimental approach to suit the nature of the problem and the objectives of the research, as the experimental approach is considered one of the best scientific research methods to solve problems. C 34 students and Division D 38 students, and the systematic random method was used to determine the two research groups, as Division (A) was chosen to be an experimental group and Division (D) a control group. research community. One of the most important conclusions is that the self-regulated learning strategy encourages students to contribute to creativity and innovation commensurate with their experiences, skills and personal talents. The self-regulated learning strategy has worked to gain the learners knowledge experience and has improved their self-organization process and the process of memorization and retrieval, and the learner has become a participant in decision-making, and the researcher recommends Paying attention to the self-regulated learning strategy as an educational strategy in physical education lessons. Emphasis on benefiting from the advantages of hip-media programs in facilitating the process of learning motor skills, especially in the early stages of learning, to reduce mistakes.Keywords: strategy, organized learning, hypermedia, handling and suppression, footballNote: the search is invalid.